Letter from Max Bredig to Georg Bredig, November 25, 1938 - Bredig, Max Albert (1938)
Letter from Max Albert Bredig (1902-1977) to his father, Georg Bredig (1868-1944). Max updates his father on his job hunt and how he celebrated Thanksgiving.
Keywords: Thanksgiving Day; Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Job hunting; Thomassen, Lars, 1896-; Chemists